Optimizing Potato Productivity in Nepal: Unveiling the Impact of Climate and Farming Practices through Econometric Insights - Poudel, Omkar; Acharya, Pradeep; Sharma, Deep Raj; Simkhada, Daya (Journal of Business and Social Sciences, 2024)
Potato production in Nepal is essential to its agricultural economy, yet is vulnerable to climatic variability and inefficient practices. This study utilized a Dynamic Ordinary Least Squares (DOLS) approach to analyze data from 1990 to 2022, incorporating variables such as temperature, rainfall, and pesticides. Data were sourced from the FAO and Climate Change Knowledge Portal. Temperature exhibited a significant positive impact on potato yield (β = 35707.52, p < 0.001), whereas rainfall’s effect was statistically insignificant (β = -28.65, p > 0.05). Pesticide use showed a strong positive correlation (β = 81.91, p < 0.001), highlighting its critical role. Nutrient management strategies, such as NPK fertilizers, were identified as effective in enhancing yields, particularly in high-altitude regions. The findings reveal the interplay of climatic factors and agronomic practices in shaping potato productivity. The dependency on pesticides raises environmental concerns, while insufficient rainfall adaptation underscores the need for supplementary irrigation systems. Region-specific, adaptive strategies such as precision irrigation and integrated pest management are recommended. Integrating climatic and agronomic factors into policymaking is crucial for enhancing potato production in Nepal. Sustainable farming practices and infrastructural support are key to ensuring economic resilience and food security.